Blood-Flow Characteristics in a Terminal Basilar Tip Aneurysm Prior to Its Fatal Rupture - Sforza, D.M.; Putman, C.M.; Scrivano, E.; Lylyk, P.; Cebral, J.R. (American Journal of Neuroradiology, 2010)
BACKGROUND AND PURPOSE: The development and validation of methods to stratify the risk of rupture of cerebral aneurysms is highly desired because current treatment risks can exceed the natural risk of rupture. Because unruptured aneurysms are typically treated before they rupture, it is very difficult to connect the proposed risk indices to the rupture of an individual aneurysm. The purpose of this case study was to analyze the hemodynamic environment of a saccular aneurysm of the terminal morphology subtype that was imaged just before its rupture and to test whether the hemodynamic characteristics would designate this particular aneurysm as at high risk. MATERIALS AND METHODS: A patient-specific CFD model was constructed from 3DRA images acquired just hours before the aneurysm ruptured. A pulsatile flow calculation was performed, and hemodynamic characteristics previously connected to rupture were analyzed. RESULTS: It was found that the aneurysm had a concentrated inflow stream, small impingement region, complex intra-aneurysmal flow structure, asymmetric flow split from the parent vessel to the aneurysm and daughter branches, and high levels of aneurysmal WSS near the impaction zone. CONCLUSIONS: The hemodynamic characteristics observed in this aneurysm right before its rupture are consistent with previous studies correlating aneurysm rupture and hemodynamic patterns in saccular and terminal aneurysms. This study supports the notion that hemodynamic information may be used to help stratify the rupture risk of cerebral aneurysms. CFDcomputational fluid dynamics3DRA3D rotational angiographyMCAmiddle cerebral arterySAHsubarachnoid hemorrhageWSSwall shear stress